(untitled) - Phan, Thị Minh Châu; Nguyễn, Thị Liên Diệp (Tp. Hồ Chí Minh, 2014)
Giáo trình của trường Đại học Kinh tế Tp. HCM theo Quyết định số 1637/ĐHKT-QLKH-HTQT ngày 06/10/2009
Keywords: Quản trị học -- Giáo trình